(untitled) (Journal of Asian Development Studies, 2024)
Gender diversity in knowledge exchange networks can be a source of innovation in organizations as it provides new insights that improve the creative process. Diversity literature provides enough evidence of the importance of utilizing mixed-gender teams to gain innovative outcomes. However, in knowledge management literature, gender diversity has been scarcely addressed. Knowledge management literature happens to be dominant, and there is a need to study the impact of gender diversity in knowledge creation processes and networks. This theoretical paper links the diversity literature to knowledge management literature and provides new understandings by considering gender as an important factor in the knowledge creation process. This paper contributes to the literature by emphasizing on exploring knowledge exchange relationships through a feminist perspective. Feminist perspective is also missing in knowledge management literature; thus, by making gender an important consideration in the socialization phase of the knowledge creation process, this paper provides a diverse perspective in knowledge management literature. Furthermore, this paper presents a conceptual model of gender-diverse knowledge exchange networks that shows the inclusion of women in knowledge exchange networks enhances the effectiveness of teams. Women are being neglected when it comes to inclusion in knowledge creating networks because of in-group bias against men and the stereotypical perception of women’s lack of technical and innovative knowledge. This paper sheds light on the importance of women’s inclusion in knowledge exchange networks by emphasizing the vitality of diversity in creating knowledge and innovation in collaborative networks and teams in organizations.